Complex illusions of peace: an interdisciplinary approach to conflict reversion in Afghanistan, 1979-2014 - Usher, S (2017)
Why do some intrastate conflict-affected states revert back to conflict, while others do not? This thesis aims to answer this question by proposing an interdisciplinary and multi-method approach to analyze the phenomenon of intrastate conflict reversion. I begin my analysis by highlighting the problematic approach of examining conflict reversion as 'frozen' or 'stuck' in equilibrium. Then, I address the shortcomings of applying 2-actor game theory models to the study of conflict reversion by linking ecological and social sciences under the theoretical framework of complexity theory. I introduce a novel model called the Competitive Efficiency Model (CEM) that embraces international relations (IR), ecology and complexity theory to simulate intrastate conflict dynamics through statistical and numerical modeling. I explain the applicability of the CEM by demonstrating mathematical principles of the model to both hypothetical scenarios and scenarios with real data. Next, I develop a set of cases from countries that experienced intrastate conflict (1946-2014). From these numerous cases, I select the case of Afghanistan (1979-2014) as an exploratory case study. The thesis contributes to existing knowledge in four core areas of conflict dynamics within the IR discipline: (1) how the misconception of equilibrium to describe conflict dynamics can be detrimental to IR and conflict scholars' ability to interpret conflict processes; (2) how an interdisciplinary approach coalesced with IR, ecology, and complexity theory, can increase our understanding of conflict reversion; (3) how population dynamics from ecology theory can be applied to better understand conflict reversion; and (4) using a mixed methods approach of statistical, numerical and a historical narrative can uncover mechanisms behind conflict reversion. This thesis concludes by summarizing key theoretical and empirical findings and main policy implications. I close by discussing some limitations within the thesis that has allowed room for future research on conflict reversion.